Postgraduate students’ gawai raya dinner 2023 - Nik Fauzi, Sheela Faizura; Abdullah, Johari; Chung, Ellen (UiTM Sarawak, 2024)
On a memorable evening of June 10, 2023, the Centre of Graduate Studies, UiTM Sarawak organized a grand Postgraduate Gawai Raya Celebration at the elegant Raia Hotel in Kuching. Gawai Raya, a combination of two significant celebrations in Sarawak which are Gawai Dayak and Hari Raya Aidilfitri that bring together people of diverse cultures and religious backgrounds in a joyous celebration of unity and harmony. It is a time for reflection, gratitude, and fostering stronger bonds within communities. The Centre of Graduate Studies at UiTM Sarawak recognized the importance of celebrating this occasion, providing postgraduate students with an opportunity to come together as a cohesive and supportive academic community.